Recent advances of optical sensors for point-of-care detection of phthalic acid esters - Zhang, Lili; Chen, Mingming; Duan, Hongwei; Bu, Quan; Dong, Xiuxiu (Frontiers in Sustainable Food Systems, 2024)
Phthalic acid esters (PAEs) are often added to plastics to enhance elasticity, transparency, durability and prolong service life as a kind of plasticizer. However, they are not chemically bonded to polymers and are difficult to degrade, which makes it easy for them to release into the environment and enter the human body from various potential sources. This results in environmental pollution and poses health risks. In order to protect ecosystem, ensure food safety and prevent disease, there is an urgent need for sensors that can achieve point-of-care detection of PAEs. Optical sensors have advantages of simplicity, portability and low cost, and have been widely applied to the detection of PAEs. In this review, we focus on introducing the recent advancements and trends in optical sensors for detection of PAEs represented by colorimetric (CL) sensors, fluorescence (FL) sensors and surface-enhanced Raman scattering (SERS) platform. Based on recognition strategies (e.g., label-free, aptamer, molecularly imprinted polymer, antibody and enzyme), the significant achievements of these optical sensors in the past five years are systematically classified and described in detail. Researchers can quickly know the development status of optical sensors for detection of PAEs in the past five years. This review highlights the strengths of each sensor type while also identifying their application limitations, providing researchers with valuable insights into future directions for optical sensor research.